RISKS OF MISSTATEMENT OF INTANGIBLE ASSETS INFORMATION AND THEIR CONSIDERATION IN THE AUDIT OF FINANCIAL STATEMENTS OF AGRICULTURAL ENTERPRISES - Yurlova, Alona (Current Problems of Sustainable Development, 2026)
The article examines the theoretical and applied aspects of the risks of misstatement of information related to intangible assets and the peculiarities of their consideration in the audit of financial statements of agricultural enterprises. It is substantiated that in the context of the digital transformation of the economy, the implementation of innovative agricultural technologies, the development of production management software systems, and the use of licenses, patents, plant variety rights, and other intellectual property objects, intangible assets acquire strategic importance in ensuring the competitiveness of agricultural businesses. It is determined that the accounting and auditing of intangible assets are associated with an increased risk of material misstatement of financial information. The main sources of such risks include the complexity of asset identification, uncertainty in determining methods for measuring their initial and fair value, difficulties in documentary confirmation of ownership rights, errors in amortization calculations, impairment risks, as well as potential fraud. Special attention is paid to the industry-specific features of agricultural enterprises, in particular the impact of production seasonality, dependence on natural and climatic conditions, rapid technological development, and the high share of intellectual resources in the structure of assets. International approaches to auditing intangible assets in accordance with IAS 38 and modern digital methods for detecting anomalies in accounting records are analyzed. A comprehensive approach to minimizing the risks of misstatement is proposed, which includes improving accounting policies, strengthening internal control, regular revaluation of assets, automation of accounting processes, and the application of risk-oriented audit procedures. Proposals for the use of Deep Learning techniques in the accounting and auditing of intangible assets of agricultural enterprises are developed. It is proven that effective auditing of intangible assets enhances the reliability of financial reporting, reduces financial and reputational risks, and ensures the sustainable development of agricultural enterprises.